The Cult of Free Verse in the Novi Sad Journal Új Symposion - Ladányi, István (Anafora, 2023)
The journal Uj Symposium was launched in Novi Sad in 1965 and after several internal or forced transformations and generational changes, it ceased to exist in 1992. In the journal’s programme of renewing Hungarian minority literature in Voj/ivodina, free verse based on the avant-garde literary tradition, along with essays and literary criticism, has gained particular importance. The paper traces the rise and literary achievements of free verse in the three decades of the journal.